Characteristics of Quality Semen, Hatching Arabic Chicken Eggs and Growth of Chicks from Crosses - Rin Orin Ningrum; Takdir Saili; la Ode Baa (Chalaza Journal of Animal Husbandry, 2018)
This study aims to evaluate and analyze the characteristics of the quality of semen, and hatching of Arab chicken eggs and the growth of crosses from chicks. This research was conducted at the Permata Farmer Group business, Wua-wua Village, Wua-wua District Kendari, Southeast Sulawesi for three months. This study uses a Completely Randomized Design which is three treatments and six replications. The parameters measured were semen quality, egg weight, egg index, fertility, DOC weight gain, feed consumption, and feed conversion. The data analysis used is Analysis of Variance. The results of this study indicate that the consequences of crossing three males did not have a significant effect (P 0.05) on the measured parameters. It can be seen in the research process which gives results that are not much different from the results of the crossing of three different males using the Arabic parent in the initial phase of production.